Vividness of Visual Imagery and Incidental Recall of Verbal Cues, When Phenomenological Availability Reflects Long-Term Memory Accessibility - D'Angiulli, Amedeo; Runge, Matthew; Faulkner, Andrew; Zakizadeh, Jila; Chan, Aldrich; Morcos, Selvana (Frontiers in Psychology, 2013)
The relationship between vivid visual mental images and unexpected recall (incidental recall) was replicated, refined and extended. In Experiment 1, participants were asked to generate mental images from imagery-evoking verbal-cues (controlled on several verbal properties) and then, on a trial-by-trial basis, rate the vividness of their images; thirty minutes later, participants were surprised with a task requiring free recall of the cues. Higher vividness ratings predicted better incidental recall of the cues than individual differences (whose effect was modest). Distributional analysis of image latencies through ex-Gaussian modeling showed an inverse relation between vividness and latency. However, recall was unrelated to image latency. The follow-up Experiment 2 showed that the processes underlying trial-by-trial vividness ratings are unrelated to the Vividness of Visual Imagery Questionnaire (VVIQ), as further supported by a meta-analysis of a randomly selected sample of relevant literature. The present findings suggest that vividness may act as an index of availability of long-term sensory traces, playing a non-epiphenomenal role in facilitating the access of those memories.